Variasi Kebugaran Jenis/Strain Trichogramma pada Telur Plutella xylostella (L.) (Lepidoptera: Plutellidae) - Siti Herlinda (Jurnal Perlindungan Tanaman Indonesia, 2005)
Laboratory experiments were conducted to evaluate fitness traits of trichogrammatid species/strains reared on eggs of the diamondback moth, Plutella xylostella (L.). The experiments used eleven trichogrammatid species/strains collected from different host species and locations. They were Trichogrammatoidea cojuangcoi Nagaraja collected from parasitized P. xylostella eggs in Jarai, Muarasiban, Kerinjing, and Bogar, Trichogrammatoidea sp. A and B collected from parasitized Helicoverpa armigera (Hubner) eggs in Bogor, Trichogrammatoidea armigera Nagaraja collected from parasitized H. armigera eggs in Bogor, Trichogramma chilonis Ishii, Trichogramma japanicum Ashmead, Trichogramma australicum Girault, and Trichogrammatoidea nana (Zehntner) collected from parasitized Chilo sp. eggs in Cinta Manis, South Sumatera. When a female of Trichogramma was constantly exposed to 100 P. xylostella eggs per day throughout her lifetime, T. cojuangcoi from Jarai produced more parasitized host eggs (50.67%) and progenies (50.67 adults/female) compared to other species/strains. Sex ratio was predominantly female, the most female progenies were produced ( 38 adults/ female) by T. cojuangcoi from Jarai. There were no significant differences in larval (0-3.27%) and pupal (0-3.75%) mortality of all species/strains. Survival emerging adults of T. japanicum (90.24%) were significantly lower than those of other species/strains. These data showed that T. cojuangcoi from Jarai could be developed as biocontrol agents of P. xylostella.